PENERAPAN METODE DESAIN HIBRID BANGUNAN LAMA DAN BARU DALAM PERANCANGAN BANGUNAN EDU-REKREATIF KISARAN - William William (Jurusan Arsitektur dan Perencanaan, 2019)
The urban routine which is not in accordance with the value of millennials in terms of recreation and socialization makes the imbalance between the city of Kisaran and its millennial generation. Millennials feel that the value in the city barely develop. Therefore, the solution is created more positive relationship between the aspects of the city and millennials. According to the issue, the Edu-Recreative Space will be established with numbers of mass areas respectively while functioning to fulfill recreational and educational facilities that are not free from socializing. The building will be formed by Hybrid method and Adaptive Re-used of the former building of swallow’s house which is a symbol of the urban trail and aspects of the city. By Hybrid method, between used buildings and new buildings where, used buildings are rearranged effectively so that they become galleries and areas for socializing with a combination of light, material and flexible space typology forms likely according to millennial characters. While, new buildings derived from a combination of contextual sites, namely ecological elements around the site and the city will be designed based on circulation typologies, given that circulation is an important aspect in maximizing educational recreational experiences and producing programs such as ecological conservation areas, galleries and other recreational areas, where the final design of the buildings which will be injected locality theme, by the morphology of the swallow nest itself. The combination of mass forms and contextual programs produces a building with a different but harmonious concept to positively and symbolically change the current perspective of the city.AbstrakRutinitas keadaan perkotaan yang tidak sesuai dengan nilai kesejamanan millenial dalam hal rekreasi dan bersosialisasi menjadikan ketidak-seimbangan antara kota Kisaran dan generasi milenialnya. Generasi milenial merasa nilai kesejamanan di kota tidak berkembang. Oleh karena itu, solusinya adalah untuk menciptakan hubungan yang lebih positif antara aspek kota dan millenial. Dengan ini, Ruang Edu-rekreatif Kisaran didirikan dengan dibekali beberapa area massa yang masing-masing berfungsi untuk memenuhi sarana rekreatif dan edukatif yang tidak luput dari hal bersosialisasi. Bangunan dibentuk dengan metode hibrid dan sistem pemakaian kembali bangunan bekas rumah burung walet yang merupakan simbol jejak urban dan aspek kota. Dengan cara hibrid antara bangunan bekas dan bangunan baru dimana, bangunan bekas ditata ulang secara efektif agar dijadikan galeri dan area untuk bersosialisasi dengan kombinasi antara cahaya, material dan bentuk tipologi ruang berundak fleksibel sesuai karakter milenial. Bangunan baru yang berasal dari kombinasi kontekstual tapak yaitu elemen ekologis sekitar tapak dan kota didesain berbasis tipologi sirkulasi, mengingat sirkulasi merupakan salah satu aspek penting dalam memaksimalkan pengalaman yang rekreatif edukatif dan menghasilkan program seperti area konservasi ekologis, galeri dan area rekreatif lainnya dimana design akhir bangunan disuntikan lokalitas tema yaitu morfologi sarang walet itu sendiri. Kombinasi antara bentuk massa dan program yang kontekstual menghasilkan suatu bangunan dengan konsep yang berbeda namun harmonis agar secara positif dan simbolis mengubah pandangan kota saat ini.